Helicobacter pylori roles in haematology disease pathogenesis - M. V. Potapova; N. A. Broyaka; K. Yu. Skvortsov; E. V. Konobeeva (Сибирский научный медицинский журнал, 2022)
Helicobacter pylori is considered to be one of the significant reasons of formation of gastroduodenal pathology. Data on the role of H. pylori in the development of extragastric diseases are confirmed by a positive effect of eradication on peripheral blood changes. In spite of this fact both aspects are still not revealed. However, undoubtedly that H. pylori persistence on gastric epithelium creates conditions for chronic local and systematic inflammation. The aim of the sur- vey was the analysis of literary data about bacterial factors in the development of iron-, vitamin B12-deficiency anaemia and thrombocytopenic purpura included by the international consensus into the circle of evedences for diagnosis and treatment of H. pylori. Material and methods. There was accomplished search of literature sources with the help of data bases PubMed, CyberLeninka, eLibrary, Google Scholar. The results of our analysis specify mechanisms of cer- tain blood diseases pathogenesis in association with H. pylori. Multiple roles of virulent strains of pathogen in anaemia and thrombocytopenic purpura include: development of erosive and ulcerative lesions of mucosa, hypoacidity, chron- ic inflammation and autoimmune response. Data about these changes in haematological syndromes and independent eradication effects on blood parameters normalisation, are controversial. Н. pylori host iron competition theory has not been found convincing confirmation. Conclusions. It is necessary to study more deeply the connection of H. pylori and haematological diseases. The dietary research and application to maintain the mucous integrity and bacterial adhesion prevention are perspective.